Research strategies in nutrition in health and disease: The failure of mechanistic research - Temple, Norman J. (Frontiers in Nutrition, 2023)
This paper critically evaluates different research methods in order to assess their value for establishing which dietary changes are most effective for protecting health and preventing disease. The evidence demonstrates that the combined use of observational studies (mainly cohort studies) and randomized controlled trials (RCTs) is the most successful strategy. Studies of the details of body mechanisms in health and disease (mechanistic research) is another commonly used research strategy. However, much evidence demonstrates that it is a far less successful strategy. In order to support the above conclusions research studies from the following areas are discussed: obesity and dietary fat; heart disease and saturated fat; the Mediterranean diet and cardiovascular disease; type 2 diabetes and dietary fiber; and cancer and micronutrients. While mechanistic research has a poor track record in nutrition, it has achieved some success in other areas of biomedical science. This is shown by examining the role of mechanistic research in the discovery of new drugs.